Preparation and application of recycling-free long-service-life coating type photocatalytic material
Coated photocatalytic materials prepared by materials such as titanium dioxide-loaded biomass carbon and conductive carbon black have solved the residual problem of tetracycline antibiotics in the water environment, and achieved efficient, economical and environmentally friendly removal effects.
Patent Information
- Application Number
- CN202411648062.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The residue of tetracycline antibiotics in the water environment leads to inhibition of algae growth, inhibition of fish embryo growth and proliferation of drug-resistant bacteria, which seriously endangers the health of humans and animals. Existing removal methods such as activated sludge method, adsorption method and photocatalytic method have difficulties and limitations.
Using titanium dioxide-laden biomass carbon as catalytic material, combining conductive carbon black and graphene as additives, using PVDF as binder, and adding N-methylpyrrolidone as regulators to prepare a recycling-free and long-life coating Covered photocatalytic material. This material is prepared by ultrasonic-assisted vacuum impregnation method, which improves the photocatalytic degradation performance of the catalytic material.
It has achieved efficient removal of tetracycline antibiotics in the water environment, improved the photocatalytic performance and service life of the catalytic materials, reduced costs, and avoided secondary pollution.
Smart Images

Figure CN119500090A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the preparation and application of a photocatalytic material, in particular to the preparation and application of a recycling-free, long-life coating type photocatalytic material. Background Art
[0002] Tetracycline antibiotics are a class of broad-spectrum antibiotics produced by actinomycetes, of which tetracycline, oxytetracycline and chlortetracycline are the most commonly used. They are widely produced and used due to their low price and broad-spectrum antibacterial effects. Russia, China and the United States are the three countries with the largest consumption of tetracycline drugs. According to statistics, China is also one of the countries with a relatively large production, use and export of tetracycline antibiotics, among which the export volume of tetracycline drugs has reached 13,400 tons.
[0003] During the widespread use of these tetracycline antibiotics, tetracycline (TC) is difficult for humans and animals to digest and absorb due to its stable structure. It is eventually discharged into the water environment in the form of urine and feces, causing antibiotic pollution residues, which seriously endangers the health of humans and animals. Its residues can cause the proliferation of drug-resistant bacteria and are assessed by the World Health Organization as one of the biggest threats to human health in the 21st century.
[0004] The main harm of tetracycline to the aquatic environment and humans is that TC has an inhibitory effect on the growth of different algae within the concentration range of 0.25-30 mg / L. When the dose reaches 30 mg / L, the growth inhibition rate of algae reaches 94%. With the exposure of TC and metabolites in the aquatic environment, the permeability of algal cells will increase, causing structural changes, including plasmolysis, deformation of thylakoid lamellae in chloroplasts, and enlargement of vacuoles. The increase in dosage will also affect the abundance and species richness of phytoplankton and zooplankton communities. When the concentration is too high, it will reduce the clarity of water and dissolved oxygen levels. The most significant of these is that TC will induce cyanobacterial blooms, increasing the density of bacteria by more than two times. In addition to affecting algae and plankton communities, it will also have many negative effects on fish communities, the most significant of which is that TC will inhibit the growth of fish embryos after being discharged into the water environment. In addition, due to the irrational use of TC, it will remain in many foods, including fish, eggs and milk. After human use, it will cause physical diseases such as liver damage, yellowing of teeth and imbalance of intestinal flora.
[0005] In general, tetracycline residues in the environment can cause a series of problems. Therefore, it is of great significance to develop an efficient and green method to remove tetracycline.
[0006] Generally speaking, conventional methods for removing antibiotics include activated sludge method, adsorption method and photocatalysis method. The activated sludge method has been widely used in industrial production due to its good water quality and stable operation. However, with the increasing number of antibiotics, the composition of wastewater has become more complex. At the same time, resistance genes will be produced during the water treatment process, which makes biological treatment very difficult. The adsorption method only transfers antibiotics to a new phase and does not completely eliminate antibiotics. It is easy to cause secondary pollution, and it is costly and has a short service life. The semiconductor photocatalytic method is considered to be an effective technical means to degrade pollutants such as antibiotics due to its strong oxidation ability, fast decomposition speed and broad spectrum of degradable substances.
[0007] Titanium dioxide is one of the most widely studied semiconductor photocatalysts due to its low cost, high efficiency, non-toxicity and stability. It can effectively degrade a variety of stable organic dyes without causing secondary pollution, and shows great application potential in the treatment of organic pollutants. However, photocatalytic materials usually exist in the form of powders, which are greatly restricted in the environment of use. How to improve its usage scenarios while retaining its good photocatalytic performance is the main focus and difficulty now. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a preparation and application of a non-recyclable, long-life coated photocatalytic material. The coated photocatalytic material of the present invention has the characteristics of simple preparation, low cost, high catalytic efficiency, long life, and easy recycling.
[0009] One of the technical solutions of the present invention:
[0010] Provided is a preparation method for a recycling-free, long-life coated photocatalytic material, which is prepared by using biomass charcoal loaded with titanium dioxide as a catalytic material, conductive carbon black and / or graphene as additives, PVDF as a binder, and N-methylpyrrolidone as a regulator. The above materials are mixed and then coated on a metal sheet to obtain the material.
[0011] Preferably, the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material comprises the following steps:
[0012] S1. Take biochar, grind it, sieve and dry it to obtain biochar powder;
[0013] S2. The biomass carbon powder is dispersed in an anhydrous ethanol solution, and then tetrabutyl titanate is added and stirred to obtain a uniform mixture, and then ultrasonically treated in an ultrasonic machine to obtain a mixture;
[0014] S3. The mixture was placed in a vacuum drying oven for vacuum impregnation, and then transferred to a blast drying oven until the solvent was completely evaporated to obtain a black powder;
[0015] S4. The black powder is placed in a furnace for pyrolysis to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0016] S5. The catalytic material, the additive and PVDF are mixed and ground, and then N-methylpyrrolidone is added and stirred to obtain a viscous slurry;
[0017] S6. The viscous slurry is evenly coated on a metal sheet, first dried naturally, and then placed in a vacuum drying oven for heat preservation, thereby obtaining the non-recyclable, long-life coated photocatalytic material.
[0018] Preferably, the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material, the preparation method of biochar described in S1 is: placing the washed and dried corn straw raw material in a furnace with a N2 protective atmosphere, heating it to 450-550°C and pyrolyzing it for 5-10 hours to obtain corn straw biochar; the screening is through a 190 mesh sieve.
[0019] Preferably, in the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material, the volume mass ratio of tetrabutyl titanate to biomass carbon powder in S2 is 5-15ml:1g; the stirring is magnetic stirring, and the stirring time is 1-2h; the ultrasonic treatment time is 20-40min.
[0020] Preferably, in the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material, the temperature in the vacuum drying oven in S3 is 70-90°C, and the immersion time is 10-15h; the temperature in the blast drying oven is 70-90°C.
[0021] Preferably, in the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material, the pyrolysis temperature in S4 is 600-700° C., and the pyrolysis time is 1-3 h.
[0022] Preferably, in the preparation of the aforementioned non-recyclable, long-life coated photocatalytic material, the mixing mass ratio of the catalytic material, additive and PVDF in S5 is 90-93:4-7:3; the mass volume ratio of the catalytic material, additive and PVDF to N-methylpyrrolidone is 1 mg:1 μl.
[0023] Preferably, in the preparation of the aforementioned recycling-free, long-life coated photocatalytic material, the insulation temperature in S5 is 70-90° C., and the insulation time is 10-15 hours.
[0024] The second technical solution of the present invention:
[0025] Provided is a recycling-free, long-life coated photocatalytic material, which is prepared according to the above method.
[0026] The third technical solution of the present invention:
[0027] Provided is an application of the aforementioned non-recycling, long-life coated photocatalytic material for catalytic degradation of tetracycline in a water environment.
[0028] Beneficial effects of the present invention:
[0029] 1. The photocatalytic material of the present invention has a simple preparation process, low cost and can be industrially produced.
[0030] 2. The present invention starts with formula design and process conditions, uses corn stalks as biochar (BC) raw materials, and adopts ultrasonic-assisted vacuum impregnation to prepare a TiO2 / BC composite material with adsorption and photocatalytic synergy, thereby improving the photocatalytic degradation performance of the catalytic material. Biochar is used as the supporting structure of TiO2. On the one hand, biochar acts as a good adsorbent to enhance the adsorption capacity of the TiO2 / BC composite material. On the other hand, it expands the light response range of TiO2, thereby achieving efficient use of light. The synergistic effect between TiO2 and BC in the TiO2 / BC composite catalytic material is used to effectively improve the separation of photogenerated electrons and holes, thereby obtaining enhanced photocatalytic performance.
[0031] 3. Compared with traditional powder-type photocatalysts, the present invention is a coated photocatalyst, which is easier to recycle and has a longer service life when used in a water environment.
[0032] 4. Compared with the traditional film-form photocatalyst, the binder of the present invention will not cover the surface of the photocatalyst. At the same time, by adding additives, the photoelectric efficiency of the catalyst can be guaranteed, thereby ensuring the photocatalytic performance.
[0033] 5. The present invention adds N-methylpyrrolidone as a regulator. On the one hand, the raw material components are mixed more evenly and the photocatalytic performance is better; on the other hand, the regulator forms micropores during the heating and evaporation process, which increases the contact area of the photocatalyst and further improves the catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Attached Figure 1 This is a real picture of the coated photocatalytic material of the present invention; DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.
[0036] Embodiments of the present invention
[0037] Example 1
[0038] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0039] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 500°C for pyrolysis for 7h to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0040] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 10 ml of tetrabutyl titanate, stir for 30 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 30 min to obtain a mixed solution;
[0041] S3. The mixture was placed in a vacuum drying oven at 80°C for 12 h, and then transferred to a forced air drying oven at 80°C until the solvent was completely evaporated to obtain a black powder;
[0042] S4. The black powder was pyrolyzed in a furnace at 650°C for 2 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0043] S5. The catalytic material, conductive carbon black and PVDF were mixed in a mass ratio of 90:7:3 and ground for 30 min, and then N-methylpyrrolidone was added in a mass volume ratio of 1 mg: 1 μl to the catalytic material, conductive carbon black and PVDF and stirred evenly to obtain a viscous slurry;
[0044] S6. The viscous slurry is evenly coated on the copper foil, first dried naturally, and then placed in a vacuum drying oven at 80° C. for 12 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0045] Example 2
[0046] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0047] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 500°C for pyrolysis for 7h to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0048] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 10 ml of tetrabutyl titanate, stir for 30 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 30 min to obtain a mixed solution;
[0049] S3. The mixture was placed in a vacuum drying oven at 80°C for 12 h, and then transferred to a forced air drying oven at 80°C until the solvent was completely evaporated to obtain a black powder;
[0050] S4. The black powder was pyrolyzed in a furnace at 650°C for 2 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0051] S5. The catalytic material, conductive carbon black and PVDF were mixed in a mass ratio of 91:6:3 and ground for 30 min, and then N-methylpyrrolidone was added in a mass volume ratio of 1 mg: 1 μl to the catalytic material, conductive carbon black and PVDF and stirred to obtain a viscous slurry;
[0052] S6. The viscous slurry is evenly coated on the copper foil, first dried naturally, and then placed in a vacuum drying oven at 80° C. for 12 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0053] Example 3
[0054] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0055] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 500°C for pyrolysis for 7h to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0056] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 10 ml of tetrabutyl titanate, stir for 30 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 30 min to obtain a mixed solution;
[0057] S3. The mixture was placed in a vacuum drying oven at 80°C for 12 h, and then transferred to a forced air drying oven at 80°C until the solvent was completely evaporated to obtain a black powder;
[0058] S4. The black powder was pyrolyzed in a furnace at 650°C for 2 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0059] S5. The catalytic material, conductive carbon black and PVDF were mixed in a mass ratio of 92:5:3 and ground for 30 min, and then N-methylpyrrolidone was added in a mass volume ratio of 1 mg: 1 μl to the catalytic material, conductive carbon black and PVDF and stirred to obtain a viscous slurry;
[0060] S6. The viscous slurry is evenly coated on the copper foil, first dried naturally, and then placed in a vacuum drying oven at 80° C. for 12 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0061] Example 4
[0062] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0063] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 500°C for pyrolysis for 7h to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0064] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 10 ml of tetrabutyl titanate, stir for 30 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 30 min to obtain a mixed solution;
[0065] S3. The mixture was placed in a vacuum drying oven at 80°C for 12 h, and then transferred to a forced air drying oven at 80°C until the solvent was completely evaporated to obtain a black powder;
[0066] S4. The black powder was pyrolyzed in a furnace at 650°C for 2 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0067] S5. The catalytic material, conductive carbon black and PVDF were mixed in a mass ratio of 93:4:3 and ground for 30 min, and then N-methylpyrrolidone was added in a mass volume ratio of 1 mg: 1 μl to the catalytic material, conductive carbon black and PVDF and stirred to obtain a viscous slurry;
[0068] S6. The viscous slurry is evenly coated on the copper foil, first dried naturally, and then placed in a vacuum drying oven at 80° C. for 12 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0069] The process methods of Experimental Examples 1-4 are the same, and the only difference is the different ratios of the catalytic material, the conductive carbon black and the PVDF. For the different photocatalytic materials prepared in Examples 1-4, the applicant conducted the following experiments:
[0070] Test method:
[0071] Tetracycline hydrochloride was used as a model pollutant to evaluate the photocatalytic degradation performance of the photocatalytic materials of Examples 1 to 4. The photocatalytic experiment was carried out in a 200 mL glass beaker connected to condensed water. A 300 W xenon lamp was used to simulate sunlight (6.6 W in the ultraviolet region and 17.6 W in the visible region) throughout the experiment. The xenon lamp was placed vertically at a fixed distance of 15 mm from the glass beaker.
[0072] In the experiment, a certain mass of the catalysts of Examples 1-4 were dispersed in a newly prepared pollutant solution, wherein the concentration of tetracycline hydrochloride was 50 mg / L and the volume was 300 mL. The resulting suspension was stirred in the dark for 1200 min and then placed in a photocatalytic reaction device for a photocatalytic experiment.
[0073] In addition, biomass carbon loaded with titanium dioxide which has not been treated by the process of the present invention is used as a powdered catalytic material and tested according to the aforementioned method as a comparative example.
[0074] The catalytic performance of each group of photocatalytic materials in the experiment was calculated by the following formula: the total amount of tetracycline removed was divided by the total amount of photocatalytic material added to obtain the unit removal amount. The specific unit removal amount data statistics are shown in Table 1 below:
[0075]
[0076] Table 1 Relationship between different ratios of binder and removal rate (catalyst: binder: conductive carbon black)
[0077]
[0078] From the statistical results of catalytic data in Table 1, at 120 min, the photocatalytic removal rate of the photocatalytic material prepared with a ratio of catalyst: binder: conductive carbon black = 93:4:3 was the best, and its unit removal amount was 31 mg / g, which was much higher than the removal amount of 13.67 mg / g of the powdered photocatalytic material.
[0079] Example 5
[0080] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0081] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 450°C for pyrolysis for 10 hours to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0082] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 5 ml of tetrabutyl titanate, stir for 20 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 20 min to obtain a mixed solution;
[0083] S3. The mixture was placed in a vacuum drying oven at 70°C for 15 h, and then transferred to a 70°C forced air drying oven until the solvent was completely evaporated to obtain a black powder;
[0084] S4. The black powder was pyrolyzed in a furnace at 600°C for 3 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0085] S5. The catalytic material, graphene and PVDF were mixed in a mass ratio of 90:7:3 and ground for 20 min, and then N-methylpyrrolidone was added in a mass volume ratio of 1 mg:1 μl with the catalytic material, conductive carbon black and PVDF and stirred evenly to obtain a viscous slurry;
[0086] S6. The viscous slurry is evenly coated on an aluminum foil, first dried naturally, and then placed in a vacuum drying oven at 70° C. for 15 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0087] Example 6
[0088] A preparation method of a non-recyclable, long-life coated photocatalytic material, comprising the following steps:
[0089] S1. The washed and dried corn straw raw material is placed in a furnace with a N2 protective atmosphere, heated to 550°C for pyrolysis for 5h to obtain corn straw biochar; the corn straw biochar is ground and passed through a 190-mesh sieve and then dried to obtain biochar powder;
[0090] S2. Disperse 1 g of biomass carbon powder in 20 ml of anhydrous ethanol solution, then add 15 ml of tetrabutyl titanate, stir for 40 min to obtain a uniform mixture, and then put it into an ultrasonic machine for ultrasonic treatment for 40 min to obtain a mixed solution;
[0091] S3. The mixture was placed in a 90°C vacuum drying oven for vacuum impregnation for 10 h, and then transferred to a 90°C blast drying oven until the solvent was completely evaporated to obtain a black powder;
[0092] S4. The black powder was pyrolyzed in a furnace at 700°C for 1 h to obtain a biomass carbon catalytic material loaded with titanium dioxide;
[0093] S5. The catalytic material, conductive carbon black and PVDF are mixed in a mass ratio of 90:7:3 and ground for 40 minutes, and then N-methylpyrrolidone is added in a mass volume ratio of 1 mg:1 μl to the mass of the catalytic material, conductive carbon black and PVDF and stirred evenly to obtain a viscous slurry.
[0094] S6. The viscous slurry is evenly coated on an iron sheet, first dried naturally, and then placed in a vacuum drying oven at 90° C. for 10 hours to obtain the non-recyclable, long-life coated photocatalytic material.
[0095] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a non-recyclable, long-life coated photocatalytic material, characterized in that: The method is prepared by using biomass carbon loaded with titanium dioxide as a catalytic material, conductive carbon black and / or graphene as an additive, PVDF as a binder, and N-methylpyrrolidone as a regulator. The above materials are mixed and then coated on a metal sheet.
2. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 1, characterized in that: The steps include: S1. Take biochar, grind it, sieve and dry it to obtain biochar powder; S2. The biomass carbon powder is dispersed in an anhydrous ethanol solution, and then tetrabutyl titanate is added and stirred to obtain a uniform mixture, and then ultrasonically treated in an ultrasonic machine to obtain a mixture; S3. The mixture was placed in a vacuum drying oven for vacuum impregnation, and then transferred to a blast drying oven until the solvent was completely evaporated to obtain a black powder; S4. The black powder is placed in a furnace for pyrolysis to obtain a biomass carbon catalytic material loaded with titanium dioxide; S5. The catalytic material, the additive and PVDF are mixed and ground, and then N-methylpyrrolidone is added and stirred to obtain a viscous slurry; S6. The viscous slurry is evenly coated on a metal sheet, first dried naturally, and then placed in a vacuum drying oven for heat preservation, thereby obtaining the non-recyclable, long-life coated photocatalytic material.
3. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: S1 The preparation method of biomass charcoal is: placing the washed and dried corn straw raw material in a furnace with N2 protective atmosphere, heating it to 450-550°C and pyrolyzing it for 5-10 hours to obtain corn straw biomass charcoal; the screening is through a 190 mesh sieve.
4. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: S2 The volume mass ratio of tetrabutyl titanate to biomass carbon powder is 5-15 ml: 1 g; the stirring is magnetic stirring, and the stirring time is 1-2 h; the ultrasonic treatment time is 20-40 min.
5. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: S3: The temperature in the vacuum drying oven is 70-90°C, and the immersion time is 10-15h; the temperature in the blast drying oven is 70-90°C.
6. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: The pyrolysis temperature in S4 is 600-700°C, and the pyrolysis time is 1-3h.
7. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: S5 The mixing mass ratio of the catalytic material, additive and PVDF is 90-93:4-7:3; the mass volume ratio of the catalytic material, additive and PVDF to N-methylpyrrolidone is 1 mg:1 μl.
8. The preparation of the non-recyclable, long-life coated photocatalytic material according to claim 2, characterized in that: The insulation temperature in S5 is 70-90° C. and the insulation time is 10-15 hours.
9. A recycling-free, long-life coated photocatalytic material, characterized in that: Prepared according to the method according to any one of claims 1 to 8.
10. Use of the non-recyclable, long-life coated photocatalytic material according to claim 9 for catalytic degradation of tetracycline in water environment.